2010
DOI: 10.1002/jbm.a.32897
|View full text |Cite
|
Sign up to set email alerts
|

Long term in vitro biostability of segmented polyisobutylene‐based thermoplastic polyurethanes

Abstract: Long term in vitro biostability of thermoplastic polyurethanes (TPUs) containing mixed polyisobutylene (PIB)/poly(tetramethylene oxide) (PTMO) soft segment was studied under accelerated conditions in 20% H(2)O(2) solution containing 0.1M CoCl(2) at 50 °C to predict resistance to metal ion oxidative degradation (MIO) in vivo. The PIB-based TPUs showed significant oxidative stability as compared to the commercial controls Pellethane 2363-55D and 2363-80A. After 12 weeks in vitro the PIB-PTMO TPUs with 10-20% PTM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…One way is to replace the soft segment of polyurethane with more stable materials, such as polyolefi ns, polysiloxane, etc. (Ward et al, 2006;Cozzens et al, 2010;Kang et al, 2010), based on the fi ndings that the soft segment played an important role in biostability . With mixed poly-isobutylene (PIB)/poly (tetramethylene oxide) (PTMO) soft segments, Cozzens synthesized a new polyurethane and demonstrated that under accelerated conditions (20% H 2 O 2 solution containing 0.1 M CoCl 2 at 50°C to predict resistance to metal ion oxidative degradation in vivo ), the PIB-based TPUs showed signifi cant oxidative stability when compared to the commercial controls, Pellethane ™ 2363-55D and 2363-80A (Cozzens et al, 2010).…”
Section: Biostability Evaluationmentioning
confidence: 99%
“…One way is to replace the soft segment of polyurethane with more stable materials, such as polyolefi ns, polysiloxane, etc. (Ward et al, 2006;Cozzens et al, 2010;Kang et al, 2010), based on the fi ndings that the soft segment played an important role in biostability . With mixed poly-isobutylene (PIB)/poly (tetramethylene oxide) (PTMO) soft segments, Cozzens synthesized a new polyurethane and demonstrated that under accelerated conditions (20% H 2 O 2 solution containing 0.1 M CoCl 2 at 50°C to predict resistance to metal ion oxidative degradation in vivo ), the PIB-based TPUs showed signifi cant oxidative stability when compared to the commercial controls, Pellethane ™ 2363-55D and 2363-80A (Cozzens et al, 2010).…”
Section: Biostability Evaluationmentioning
confidence: 99%
“…Recently, PIB-based TPUs (including the similar segmented polyureas and polyurethaneureas) have been successfully synthesized (7)(8)(9)(10)(11). As expected, PIB-based TPUs show significantly enhanced biostability (11,12), and their biocompatibility is also comparable to conventional TPUs based on polyether or polyester (13). However, these TPUs exhibited very poor mechanical strength, which limits their practical applications (7)(8)(9)14).…”
Section: Introductionmentioning
confidence: 94%
“…To solve this problem, TPUs with the SS based on polyisobutylene (PIB), which is wellknown for superior biostability (7), have been successfully developed (8)(9)(10). Although these PIB-based TPUs show significantly enhanced biostability (11,12), their mechanical strength is low (8,9,13,14), and TPUs with high weight fraction of the HS cannot be processed below the decomposition temperature (9). It was later demonstrated that the mechanical properties of PIB-based TPUs can be significantly enhanced by incorporating a small amount of polyether diols into the SS (9,10,15).…”
Section: Introductionmentioning
confidence: 98%
“…These results provide a very promising approach to prepare biostable TPUs with high mechanical strength. However, since the introduction of polyether diol still decreases the biostability of PIB/PTMO-based TPUs (11), it will be Downloaded by [Umeå University Library] at 21:18 05 April 2015 highly desirable if the mechanical properties of the PIBbased TPUs can be improved without incorporating any ether or ester structure.…”
Section: Introductionmentioning
confidence: 99%